Ethical Governance for Sustainable Development in Higher Education Institutions: Lessons From a Small-Scale University - Freitas, Ana Costa (2018)
In contemporary societies, higher education institutions face the impact of globalization, which is mainly demanding in imposing and shaping ethical practices. While higher education systems and dynamics cannot be understood apart from this broader context, its primary focus seems to remain as equal as ever: the creation of knowledge-based societies and economies, education and the creation of socially responsible citizens. Against this background, this chapter aims to present and critically discuss the strategies implemented in a higher education institution towards building a culture of integrity. The empirical focus is a small-scale university located in southern Europe, peripheral to prominent universities and major countries.